THE ROLE OF AGRICULTURAL ECONOMICS IN POLICY FORMATION: INVESTIGATING THE INTERACTIONS BETWEEN GOVERNMENT DECISIONS AND MARKET DYNAMICS - Revi Sesario; Mahamat Saleh; Putu Fajar Kartika Lestari (Techno Agriculturae Studium of Research, 2026)
Agricultural systems operate within complex economic environments shaped by government interventions, market forces, global trade dynamics, and food security concerns. Increasing market volatility, climate-related disruptions, resource constraints, and evolving consumer demands have intensified the need for effective agricultural policies capable of balancing economic efficiency, social welfare, and sustainable development objectives. Agricultural economics has emerged as a critical discipline that provides analytical tools for understanding market behavior and supporting evidence-based policymaking. This study aims to examine the role of agricultural economics in policy formation and to investigate the interactions between government decisions and agricultural market dynamics. A qualitative research design based on a systematic literature review and comparative policy analysis was employed. Data were collected from peer-reviewed journal articles, policy reports, governmental publications, and institutional documents published between 2010 and 2025. Findings indicate that agricultural economics significantly contributes to policy effectiveness by improving resource allocation, evaluating policy alternatives, anticipating market responses, and reducing unintended economic distortions. Policy consistency, institutional capacity, market responsiveness, and information availability emerged as key factors influencing the relationship between government interventions and market outcomes. Evidence further demonstrates that agricultural markets actively adapt to policy changes through adjustments in production decisions, investment behavior, and resource utilization. The study concludes that agricultural economics functions as a strategic bridge between public policy objectives and market realities, enabling governments to formulate more adaptive, efficient, and evidence-based policies capable of promoting agricultural competitiveness, food security, and sustainable rural development.